Hjørnestenene i den danske kriminalforsorg: - Linda Kjær Minke (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract The principles of normalisation and openness are cornerstones of modern prison philosophy. Normalisation involves making prison life as similar as possible to normal outside life and openness counteracts the negative effects of the total institution (Rentzmann, 1996). Both normalisation and openness imply that it should be the norm to place a person in an open prison. He or she should only be placed in a closed prison if there is a concrete, real risk of escape or if the prisoner is considered dangerous. The question is: does the Danish prison system in the era of the millennium still pay tribute to these two cornerstones when it comes to prisoner placement and furloughs? Since sentence length and disciplinary offences can determine both prisoner placement and prison furloughs, the article also explores developments in determinate sentencing and disciplinary punishment. Based on statistics and legislation, the analysis reveals that the severity of penalties increased during the period 2002-2019, e.g., average sentence length increased, more prisoners were placed in closed prisons, fewer prison furloughs were permitted, and more prisoners were exposed to disciplinary punishment. These developments can be explained by laws and rules implemented to deal with gang-related crime and gang-connected prisoners, who make up about 10 percent of the total prison population. While these strict laws and rules are designed to discipline the few, they have influenced the many and undermined the basic principles of normalisation and openness in Danish prisons.